Growth and morphological analysis of segmented AuAg alloy nanowires created by pulsed electrodeposition in ion-track etched membranes - Schubert, Ina; Burr, Loic; Trautmann, Christina; Toimil-Molares, Maria Eugenia (Beilstein Journal of Nanotechnology, 2015)
Background: Multicomponent heterostructure nanowires and nanogaps are of great interest for applications in sensorics. Pulsed electrodeposition in ion-track etched polymer templates is a suitable method to synthesise segmented nanowires with segments consisting of two different types of materials. For a well-controlled synthesis process, detailed analysis of the deposition parameters and the size-distribution of the segmented wires is crucial.Results: The fabrication of electrodeposited AuAg alloy nanowires and segmented Au-rich/Ag-rich/Au-rich nanowires with controlled composition and segment length in ion-track etched polymer templates was developed. Detailed analysis by cyclic voltammetry in ion-track membranes, energy-dispersive X-ray spectroscopy and scanning electron microscopy was performed to determine the dependency between the chosen potential and the segment composition. Additionally, we have dissolved the middle Ag-rich segments in order to create small nanogaps with controlled gap sizes. Annealing of the created structures allows us to influence their morphology.Conclusion: AuAg alloy nanowires, segmented wires and nanogaps with controlled composition and size can be synthesised by electrodeposition in membranes, and are ideal model systems for investigation of surface plasmons.
Keywords: AuAg alloy; cyclic voltammetry; electrodeposition; ion-track technology; nanogaps; segmented nanowires

(untitled) - Piraux, L.; George, J.; Despres, J.; Leroy, C.; Ferain, E.; Legras, R.; Ounadjela, K.; Fert, A. (Appl. Phys. Lett., 1994)

(untitled) - Liu, K.; Nagodawithana, K.; Searson, P. C.; Chien, C. L. (Phys. Rev. B, 1995)

(untitled) - Bentley, A. K.; Trethewey, J. S.; Ellis, A. B.; Crone, W. C. (Nano Lett., 2004)

(untitled) - Mock, J. J.; Oldenburg, S. J.; Smith, D. R.; Schultz, D. A.; Schultz, S. (Nano Lett., 2002)

(untitled) - Zhu, J. (Nanoscale Res. Lett., 2009)

(untitled) - Goldberger, J.; He, R.; Zhang, Y.; Lee, S.; Yan, H.; Choi, H.-J.; Yang, P. (Nature, 2003)

(untitled) - Keating, C. D.; Natan, M. J. (Adv. Mater., 2003)

(untitled) - Nicewarner-Peña, S. R.; Carado, A. J.; Shale, K. E.; Keating, C. D. (J. Phys. Chem. B, 2003)

(untitled) - Zhang, D.; Liu, Z.; Han, S.; Li, C.; Lei, B.; Stewart, M. P.; Tour, J. M.; Zhou, C. (Nano Lett., 2004)

(untitled) - Chong, Y. T.; Görlitz, D.; Martens, S.; Yau, M. Y. E.; Allende, S.; Bachmann, J.; Nielsch, K. (Adv. Mater., 2010)

(untitled) - Herderick, E. D.; Tresback, J. S.; Vasiliev, A. L.; Padture, N. P. (Nanotechnology, 2007)

(untitled) - Lauhon, L. J.; Gudiksen, M. S.; Wang, D.; Lieber, C. M. (Nature, 2002)

(untitled) - Law, M.; Greene, L. E.; Radenovic, A.; Kuykendall, T.; Liphardt, J.; Yang, P. (J. Phys. Chem. B, 2006)

(untitled) - Greene, L. E.; Law, M.; Yuhas, B. D.; Yang, P. (J. Phys. Chem. C, 2007)

(untitled) - Czaban, J. A.; Thompson, D. A.; LaPierre, R. R. (Nano Lett., 2008)

Ion Beams in Nanoscience and Technology - Trautmann, C. (Micro-and nanoengineering with ion tracks, 2010)

(untitled) - Toimil-Molares, M. E. (Beilstein J. Nanotechnol., 2012)

(untitled) - Picht, O.; Müller, S.; Alber, I.; Rauber, M.; Lensch-Falk, J.; Medlin, D. L.; Neumann, R.; Toimil-Molares, M. E. (J. Phys. Chem. C, 2012)

(untitled) - Müller, S.; Schötz, C.; Picht, O.; Sigle, W.; Kopold, P.; Rauber, M.; Alber, I.; Neumann, R.; Toimil-Molares, M. E. (Cryst. Growth Des., 2012)

(untitled) - Schubert, I.; Sigle, W.; Burr, L.; van Aken, P.; Trautmann, C.; Toimil-Molares, M. (Adv. Mater. Lett., 2015)

(untitled) - Wang, L.; Yu-Zhang, K.; Metrot, A.; Bonhomme, P.; Troyon, M. (Thin Solid Films, 1996)

(untitled) - Hernández, R. M.; Richter, L.; Semancik, S.; Stranick, S.; Mallouk, T. E. (Chem. Mater., 2004)

(untitled) - Chakarvarti, S. K.; Vetter, J. (J. Micromech. Microeng., 1993)

(untitled) - Valizadeh, S.; Hultman, L.; George, J. M.; Leisner, P. (Adv. Funct. Mater., 2002)

(untitled) - Wang, A. A.; Lee, J.; Jenikova, G.; Mulchandani, A.; Myung, N. V.; Chen, W. (Nanotechnology, 2006)

(untitled) - Van Hoang, N.; Kumar, S.; Kim, G.-H. (Nanotechnology, 2009)

(untitled) - Burdick, J.; Alonas, E.; Huang, H.-C.; Rege, K.; Wang, J. (Nanotechnology, 2009)

(untitled) - Chen, M.; Chien, C.-L.; Searson, P. C. (Chem. Mater., 2006)

(untitled) - Cho, J. U.; Wu, J.-H.; Min, J. H.; Lee, J. H.; Liu, H.-L.; Kim, Y. K. (J. Magn. Magn. Mater., 2007)

(untitled) - Lee, J. H.; Wu, J. H.; Liu, H. L.; Cho, J. U.; Cho, M. K.; An, B. H.; Min, J. H.; Noh, S. J.; Kim, Y. K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Fedorov, F. S.; Mönch, I.; Mickel, C.; Tschulik, K.; Zhao, B.; Uhlemann, M.; Gebert, A.; Eckert, J. (J. Electrochem. Soc., 2013)

(untitled) - Choi, J.-r.; Oh, S. J.; Ju, H.; Cheon, J. (Nano Lett., 2005)

(untitled) - Wang, J. (J. Mater. Chem., 2008)

(untitled) - Hunyadi, S. E.; Murphy, C. J. (J. Mater. Chem., 2006)

(untitled) - Lee, K.-S.; El-Sayed, M. A. (J. Phys. Chem. B, 2006)

(untitled) - Liu, M.; Guyot-Sionnest, P. (J. Phys. Chem. B, 2004)

(untitled) - Nicewarner-Peña, S. R.; Freeman, R. G.; Reiss, B. D.; He, L.; Peña, D. J.; Walton, I. D.; Cromer, R.; Keating, C. D.; Natan, M. J. (Science, 2001)

(untitled) - Qin, L.; Park, S.; Huang, L.; Mirkin, C. A. (Science, 2005)

(untitled) - Osberg, K. D.; Schmucker, A. L.; Senesi, A. J.; Mirkin, C. A. (Nano Lett., 2011)

(untitled) - Zhou, X.; Shade, C. M.; Schmucker, A. L.; Brown, K. A.; He, S.; Boey, F.; Ma, J.; Zhang, H.; Mirkin, C. A. (Nano Lett., 2012)

(untitled) - Qin, L.; Zou, S.; Xue, C.; Atkinson, A.; Schatz, G. C.; Mirkin, C. A. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Wei, W.; Li, S.; Qin, L.; Xue, C.; Millstone, J. E.; Xu, X.; Schatz, G. C.; Mirkin, C. A. (Nano Lett., 2008)

(untitled) - Osberg, K. D.; Rycenga, M.; Harris, N.; Schmucker, A. L.; Langille, M. R.; Schatz, G. C.; Mirkin, C. A. (Nano Lett., 2012)

(untitled) - Chen, X.; Guo, Z.; Yang, G.-M.; Li, J.; Li, M.-Q.; Liu, J.-H.; Huang, X.-J. (Mater. Today, 2010)

(untitled) - Alber, I.; Sigle, W.; Müller, S.; Neumann, R.; Picht, O.; Rauber, M.; van Aken, P. A.; Toimil-Molares, M. E. (ACS Nano, 2011)

(untitled) - Osberg, K. D.; Harris, N.; Ozel, T.; Ku, J. C.; Schatz, G. C.; Mirkin, C. A. (Nano Lett., 2014)

(untitled) - Smith, P. A.; Nordquist, C. D.; Jackson, T. N.; Mayer, T. S.; Martin, B. R.; Mbindyo, J.; Mallouk, T. E. (Appl. Phys. Lett., 2000)

(untitled) - Liu, S.; Tok, J. B.-H.; Bao, Z. (Nano Lett., 2005)

(untitled) - Uran, C.; Unal, E.; Kizil, R.; Demir, H. V. (IEEE J. Quantum Electron., 2009)

(untitled) - Trautmann, C. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1995)

(untitled) - Ji, C.; Oskam, G.; Ding, Y.; Erlebacher, J. D.; Wagner, A. J.; Searson, P. C. (J. Electrochem. Soc., 2003)

(untitled) - Ghosh, S. K.; Grover, A. K.; Chowdhury, P.; Gupta, S. K.; Ravikumar, G.; Aswal, D. K.; Kumar, M. S.; Dusane, R. O. (Appl. Phys. Lett., 2006)

(untitled) - Ghosh, S. K. (Electrochim. Acta, 2008)

(untitled) - Uhlemann, M.; Gebert, A.; Herrich, M.; Krause, A.; Cziraki, A.; Schultz, L. (Electrochim. Acta, 2003)

(untitled) - Huo, S.; Schwarzacher, W. (Phys. Rev. Lett., 2001)

(untitled) - Hasan, N. M.; Mallett, J. J.; dos Santos Filho, S. G.; Pasa, A. A.; Schwarzacher, W. (Phys. Rev. B, 2003)

(untitled) - Erlebacher, J.; Aziz, M. J.; Karma, A.; Dimitrov, N.; Sieradzki, K. (Nature, 2001)

(untitled) - Erlebacher, J.; Seshadri, R. (MRS Bull., 2009)

(untitled) - Ji, C.; Searson, P. C. (Appl. Phys. Lett., 2002)

(untitled) - Nichols, F. A. (J. Mater. Sci., 1976)

(untitled) - Alber, I.; Sigle, W.; Demming-Janssen, F.; Neumann, R.; Trautmann, C.; van Aken, P. A.; Toimil-Molares, M. E. (ACS Nano, 2012)